Organic geochemical studies of modern microbial mats from Shark Bay: Part I: Influence of depth and salinity on lipid biomarkers and their isotopic signatures - Pages, Anais; Grice, Kliti; Ertefai, Tobias; Skrzypek, G.; Jahnert, Ricardo; Greenwood, Paul (John Wiley & Sons Ltd, 2014)
The present study investigated the influence of abiotic conditions on microbial mat communities from Shark Bay, a World Heritage area well known for a diverse range of extant mats presenting structural similarities with ancient stromatolites. The distributions and stable carbon isotopic values of lipid biomarkers [aliphatic hydrocarbons and polar lipid fatty acids (PLFAs)] and bulk carbon and nitrogen isotope values of biomass were analysed in four different types of mats along a tidal flat gradient to characterize the microbial communities and systematically investigate the relationship of the above parameters with water depth. Cyanobacteria were dominant in all mats, as demonstrated by the presence of diagnostic hydrocarbons (e.g. n-C17 and n-C17:1). Several subtle but important differences in lipid composition across the littoral gradient were, however, evident. For instance, the shallower mats contained a higher diatom contribution, concordant with previous mat studies from other locations (e.g. Antarctica).Conversely, the organic matter (OM) of the deeper mats showed evidence for a higher seagrass contribution [high C/N, 13C-depleted long-chain n-alkanes]. The morphological structure of the mats may have influenced CO2 diffusion leading to more 13C-enriched lipids in the shallow mats. Alternatively, changes in CO2 fixation pathways, such as increase in the acetyl COA-pathway by sulphate-reducing bacteria, could have also caused the observed shifts in δ13C values of the mats. In addition, three smooth mats from different Shark Bay sites were analysed to investigate potential functional relationship of the microbial communities with differing salinity levels. The C25:1 HBI was identified in the high salinity mat only and a lower abundance of PLFAs associated with diatoms was observed in the less saline mats, suggesting a higher abundance of diatoms at the most saline site. Furthermore, it appeared that the most and least saline mats were dominated by autotrophic biomass using different CO2 fixation pathways.